2006
DOI: 10.2353/jmoldx.2006.060016
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of B- and T-Cell Gene Rearrangements and Epstein-Barr Virus in T-Cell Lymphomas

Abstract: We report on a series of 58 cases of angioimmunoblastic T-cell lymphoma (AILT) and 59 cases of peripheral Tcell lymphoma, unspecified (PTCL-NOS). Subsets of cases from both diagnostic groups were complicated by associated B-cell proliferations, and we performed Band T-cell clonality studies and in situ hybridization for Epstein-Barr virus (EBV) to investigate the relationship between B-cell proliferation, B-cell clonality, and EBV. Using multiplex polymerase chain reaction assays based on the BIOMED-2 collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…Two of three discordant samples had clonal rearrangements of both IgH and TCRγ, which has been documented previously in canine and human lymphoid tumours (Burnett et al, 2003, Tan et al, 2006, Valli et al, 2006, Bagg, 2006). In humans, the clonal rearrangements may arise from separate populations of cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Two of three discordant samples had clonal rearrangements of both IgH and TCRγ, which has been documented previously in canine and human lymphoid tumours (Burnett et al, 2003, Tan et al, 2006, Valli et al, 2006, Bagg, 2006). In humans, the clonal rearrangements may arise from separate populations of cells.…”
Section: Discussionsupporting
confidence: 77%
“…In humans, the clonal rearrangements may arise from separate populations of cells. In T-cell tumours, a clonal B-cell population may arise secondary to immune dysfunction, usually in association with EBV infection (Luzzatto et al, 2005, Tan et al, 2006) and transform to produce a tumour containing malignant B- and T-cells (Zettl et al, 2002). In B-cell tumours, a restricted T-cell response may generate clonal TCR rearrangements (Sze, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although clonal immunoglobulin gene rearrangement can be found in as many as 20–30 % of AITL cases [5, 12], the expanded B cell component is generally polytypic and regarded reactive in nature, while subsequent development of EBV-associated B cell lymphomas in patients with AITL is rare. To our knowledge, only 21 cases of AITL with histologic progression to EBV-associated B cell lymphoma, involving nodal (13/21) and extranodal (8/21) sites, have been described in English literature [1422, 24].…”
Section: Discussionmentioning
confidence: 99%
“…AITL was previously considered an atypical reactive process termed angioimmunoblastic lymphadenopathy with dysproteinemia (AILD), with propensity of progression to frank T cell lymphoma [2, 3]. However, subsequent genetic studies demonstrated presence of monoclonal T cell receptor gene rearrangements as well as clonal cytogenetic abnormalities in vast majority of the cases, supporting the neoplastic nature of the proliferation from the onset [4, 5]. Consequently, AITL is recognized as a distinct clinicopathologic entity in the current WHO classification [6].…”
Section: Introductionmentioning
confidence: 99%
“…These multiplex PCRs are based on a European collaborative study (BIO-MED Concerted Action). The polymerase chain reaction (PCR) was performed according to the manufacturer's protocols and as previously reported [17]. Briefly, DNA was obtained from paraffin-embedded tissue blocks using a DNease tissue kit (Qiagen, Valencia, CA).…”
Section: T-cell Clonality Studiesmentioning
confidence: 99%